Resveratrol decreases fructose‐induced oxidative stress, mediated by NADPH oxidase via an AMPK‐dependent mechanism. (June 2014) - Cheng, Pei‐Wen; Ho, Wen‐Yu; Su, Yu‐Ting; Lu, Pei‐Jung; Chen, Bo‐Zone; Cheng, Wen‐Han; Lu, Wen‐Hsien; Sun, Gwo‐Ching; Yeh, Tung‐Chen; Hsiao, Michael; Tseng, Ching‐Jiunn
<x xml:space="preserve">Abstract</x> Background and Purpose Oxidative stress is an important pathogenic factor in the development of hypertension. Resveratrol, the main antioxidant in red wine, improves NO bioavailability and prevents cardiovascular disease. The aim of this study was to examine whether resveratrol decreases the generation of reactive oxygen species (ROS), thereby reducing BP in rats with fructose‐induced hypertension. Experimental Approach Rats were fed 10% fructose with or without resveratrol (10 mg·kg−1·day−1) for 1 week or for 4 weeks with resveratrol treatment beginning at week 2; systolic BP (SBP) was measured by tail‐cuff method. Endogenous in vivo O2− production in the nucleus tractus solitarii (NTS) was determined with dihydroethidium. Real‐time PCR and immunoblotting analyses were used to quantify RNA and protein expression levels. Key Results In fructose‐fed rats, ROS levels in the NTS were higher, whereas the NO level was significantly decreased. Also, RNA and protein levels of NADPH oxidase subunits (p67, p22‐phox) were elevated, superoxide dismutase 2 (SOD2) reduced and AMP‐activated PK (AMPK) T172 phosphorylation levels in the NTS were lower in fructose‐fed rats. Treatment with the AMPK activator resveratrol decreased levels of NADPH oxidase subunits and ROS, and increased NO and SOD2 levels in the NTS of fructose‐fed rats. Administration of resveratrol, in combination with fructose at week 0 and later at week 2, significantly reduced the SBP of fructose‐fed rats. Conclusions and Implications Collectively, resveratrol decreased BP through the phosphorylation of AMPK, Akt and neuronal NOS in fructose‐fed rats. These novel findings suggest that resveratrol may be a potential pharmacological candidate for the treatment of hypertension.